Basal leaf removal to reduce fruitset and induce smaller and looser clusters in variety Trincadeira with compact bunches - Bazzano, Lorenza (2016)
Mestrado Vinifera Euromaster - Viticulture and Enology - Instituto Superior de Agronomia - UL / Institutt National D'Etudes Superieures Agronomiques de Montpellier